Preparation of Activated Charcoal Adsorbent from Waste Tire - Jha, Vinay Kumar; Subedi, Kiran (Journal of Nepal Chemical Society, 2012)
Activated charcoal was prepared from waste tire by using pyrolysis technique in three different atmospheres, viz, air, nitrogen and a combined atmosphere of nitrogen and water (steam). Methylene blue was then adsorbed on to these activated charcoals and the kinetics of adsorption was also studied. The adsorption isotherms of methylene blue were simulated by the mathematical equations of Langmuir and Freundlich. The Langmuir isotherms were found to have better fitting than that of Freundlich. The Qmax values obtained from Langmuir model were 0.032, 0.036, and 0.092 mmol/g for the activated charcoals prepared in air, nitrogen and nitrogen and water (steam), respectively. The overall reaction was found to be pseudo-second order with the rate constant of 4.2 × 10-2 L g/(mmolmin). The equilibrium adsorption value obtained from the kinetics data i.e. 0.072 (mmol/g) was found to be comparable with that obtained from Langmuir model. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6437 J. Nepal Chem. Soc., Vol. 27, 2011 19-25 Uploaded date: 16 July, 2012